HMF: Simple Type Inference for First-Class Polymorphism - Leijen, Daan (13th ACM symp. of the International Conference on Functional Programming (ICFP'08), 2008)
HMF is a conservative extension of Hindley-Milner type inference with first-class polymorphism and regular System F types. The system distinguishes itself from other proposals with simple type rules and a very simple type inference algorithm that is just a small extension of the usual Damas-Milner algorithm. Given the relative simplicity and expressive power, we feel that HMF can be a very attractive type system in practice. Extended version with proofs available as Microsoft Research technical report MSR-TR-2007-118, Sep 2007 (see link below)